Infark Miokard Akut Tanpa Elevasi Segmen ST pada Wanita Usia Muda dengan Ketoasidosis Diabetik - Rahmawati, Novi; Prasetya, Indra; Prastya, Andhika (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Diabetic ketoacidosis (DKA) is the primary acute metabolic complication of diabetes mellitus (DM), specifically type 2 DM. Individuals with acute coronary syndrome (ACS) have a twice-higher incidence compared to non-diabetic individuals. In people with DM, ACS is responsible for 75% of mortality. This case report investigates a 34-year-old female patient who presented at the Emergency Department of Saiful Anwar Malang Hospital with acute gastrointestinal symptoms of diarrhea and moderate to severe dehydration. Patients with a history of type 2 DM were first diagnosed at the age of 28. The laboratory tests indicated the presence of high blood sugar levels, metabolic acidosis, and ketone-positive. During DKA hydration management, patients have atypical angina with ECG changes from sinus tachycardia to episodic Total AV Block (TAVB) spontaneous termination, increased cardiac enzyme HS (high-sensitivity) Troponin I. Patients diagnosed with acute Non-elevated Segment ST Myocardial Infarction (NSTEMI) very high risk criteria. The patient performed an immediate invasive strategy and promptly identified stenosis in three coronary arteries, with the target lesion being in the Right Coronary Artery (RCA). Subsequently, a drug-eluting stent was implanted in the osteal to mid RCA. Efficient and timely management strategies that prioritize accuracy and simultaneous therapy for cases of DKA and NSTEMI to achieve optimal outcomes.